How to think about God : a guide for the 20th-century pagan - Adler, Mortimer Jerome, 1902-2001 (New York : MacMillan, 1980)
Dr. Adler, in his discussion, extends and modernizes the argument for the existence of God developed by Aristotle and Aquinas. Without relying on faith, mysticism, or science (none of which, according to Dr. Adler, can prove or disprove the existence of God), he uses a rationalist argument to lead the reader to a point where he or she can see that the existence of God is not necessarily dependent upon a suspension of disbelief. Dr. Adler provides a nondogmatic exposition of the principles behind the belief that God, or some other supernatural cause, has to exist in some form. Through concise and lucid arguments, Dr. Adler shapes a highly emotional and often erratic conception of God into a credible and understandable concept for the lay person. -- Publisher's description.
Includes bibliographical references (p. 172-175).
Keywords: God (Christianity).; God -- Proof